Calycosin Influences the Metabolism of Five Probe Drugs in Rats - Wu M; Lin Y; Wei Y; Du H; Ying X; Tan W; Tang B (Dove Medical Press, 2020)
Mei-ling Wu, Yi-ping Lin, Yan-li Wei, Hong-jian Du, Xiao-qian Ying, Wen-zhuang Tan, Bi-e Tang Faculty of Medicine, Jinhua Polytechnic, Zhejiang, People’s Republic of ChinaCorrespondence: Bi-e TangFaculty of Medicine, Jinhua Polytechnic, No. 1188 Wuzhou Street, Jinhua City, Zhejiang Provinc, People’s Republic of ChinaEmail tangbiejh@163.comBackground: Calycosin (CAL), a type of O-methylated isoflavone extracted from the herb Astralagusmembranaceus (AM), is a bioactive chemical with antioxidative, antiphlogistic and antineoplastic activities commonly used in traditional alternative Chinese medicine. AM has been shown to confer health benefits as an adjuvant in the treatment of a variety of diseases.Aim: The main objective of this study was to determine whether CAL influences the cytochrome P450 (CYP450) system involved in drug metabolism.Methods: Midazolam, tolbutamide, omeprazole, metoprolol and phenacetin were selected as probe drugs. Rats were randomly divided into three groups, specifically, 5% Carboxymethyl cellulose (CMC) for 8 days (Control), 5% CMC for 7 days + CAL for 1 day (single CAL) and CAL for 8 days (conc CAL), and metabolism of the five probe drugs evaluated using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS).Results: No significant differences were observed for omeprazole and midazolam, compared to the control group. Tmax and t1/2 values of only one probe drug, phenacetin, in the conc CAL group were significantly different from those of the control group (Tmax h: 0.50± 0.00 vs 0.23± 0.15; control vs conc CAL). Cmax of tolbutamide was decreased about two-fold in the conc CAL treatment group (conc vs control: 219.48 vs 429.56, P< 0.001).Conclusion: Calycosin inhibits the catalytic activities of CYP1A2, CYP2D6 and CYP2C9. Accordingly, we recommend caution, particularly when combining CAL as a modality therapy with drugs metabolized by CYP1A2, CYP2D6 and CYP2C9, to reduce the potential risks of drug accumulation or ineffective treatment.Keywords: calycosin, herb-drug interactions, UPLC-MS/MS, cocktail, CYP450